Human Relations in Jane Austen’s novel Pride and Prejudice - Alquraidhy, Khalil (International Journal of Language and Literary Studies, 2022)
This research study aims to highlight and discuss Human Relations in Jane Austen’s novel Pride and Prejudice, in which she has selected the basic unit of human relationship, the family. In the family there are several forms of relationships among them the most fundamental relationship is in terms of love and marriage which form the basic theme of the novel Pride and Prejudice along with the theme of human relations. By a close reading of the novel, the present study will analyse and discuss parents and children’s relations, friends’ relations, and other minor relations. To discuss parents and children’s relations the focus will be on the relationship between Mr. Bennet, the father and Elizabeth, the daughter. From a vantage point of view, the daughter reviews the relationship between her father and mother as husband and wife in terms of their love and marriage. She finds it damaging to the family and rejects it. Steering clear of them she treads over her own path. In other words, she doesn’t accept her parents as role–models. What is true, socially, and artistically, about the relationship between parents and daughters also holds true about the relationship between the friends, and it has also been discussed and analyzed in this research study. Charlotte Lucas has a realist’s idea of marriage. Elizabeth has an idealist’s idea of marriage. It is suggested that the ideal becomes perfect only when it accommodates the real. There are a few other minor relations developed around the characters of Wickham and the Gardiners. They play an active role in further clarifying and reinforcing Elizabeth’s vision of a marriage with affection.